2009
DOI: 10.1007/bf03345708
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic parameters after BioEnterics Intragastric Balloon placement in obese patients

Abstract: These data show that BIB improves anthropometric parameters, with reduction of fat mass and preservation of fat-free mass, as well as insulin resistance, but not other metabolic features. The observed change in dietary habits, with a relative increase in lipid intake, once BIB is removed, might favor body weight regain and impact negatively on body weight composition and the other traits of the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
0
24
1
Order By: Relevance
“…A previous study in obese adults with IB also found no changes in these biomarkers. However, evaluating dietary food intake, they observed a reduction in energy and carbohydrate and an increase in fat intake [26].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in obese adults with IB also found no changes in these biomarkers. However, evaluating dietary food intake, they observed a reduction in energy and carbohydrate and an increase in fat intake [26].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies have been uncontrolled and/or retrospective (13)(14)(15)(16)(17)(18)(19)(20). Only three studies published to date employed a prospective, randomized, controlled trial design with a long-term follow-up (!1 year) (21-23); two of which included the use of more than one IGB (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Attention should be paid to the reduction of the surface of visceral adipose tissue, which highly correlates with the development of metabolic diseases [20]. Similar profits from using BIB treatment were observed by scientists from other countries [21][22][23]. The consequences of obesity for the function of cardiovascular system mainly depend on the distribution of adipose tissue.…”
Section: Discussionmentioning
confidence: 74%
“…Numerous studies confirm the effectiveness of bariatric methods in the reduction of body mass and glucose level in blood. Moreover, the improvement in heart and metabolic profile in obese children was also reported [21][22][23].…”
Section: Discussionmentioning
confidence: 78%